ANALISIS MAKNA ZAKAT DALAM AL-QURAN: Kajian Teks dan Konteks - Alim, Hadi Nur (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Zakat is one of the main pillars of Islamic teachings, which instructs Muslims to give part of their wealth to the needy. The meaning of zakat in the Qur'an has been the subject of significant research in Islamology, with many different interpretations of the Qur'anic verses relating to zakat. Therefore, this research aims to explore this further and reveal the meaning of zakat contained in the text of the Koran. This research uses the Al-Quran text analysis method, with a tafsir (interpretation) approach by analyzing the verses of the Al-Quran which specifically mention zakat and conducting a theological analysis to understand the role of zakat in Islam and its impact on the lives of Muslims. Data for this research was obtained from the Al-Quran and various literary sources relevant to the theme of zakat in Islam. We also refer to the interpretations of scholars and relevant previous research. The research results show that the concept of zakat in the Koran is the obligation to give part of one's wealth to those in need, with the main aim of creating social justice, reducing economic inequality, and strengthening social ties in Muslim society. Zakat also has a moral and spiritual dimension, teaching values ​​such as generosity, empathy and solidarity.